Study on the Development of Spiral babylonia snail Tiger Snail Juvenil Eggs (Babylonia spirata Linnaeus, 1758) in the Laboratory - Muhammad Fatoni; Delianis Pringgenies; Ali Djunaedi (Masyarakat Moluska Indonesia, 2020)
Several marine gastropods are known to have high economic value, one of which is the Spiral babylonia snail. They commonly exploited for meat, shell, or operculum. Tiger snail meat is commonly exported and consumed by fishermen. Its shell is used as a material for industrial lime and for omamen. Operculum is commonly used as a medicinal and perfume ingredient). However, the recent production has decreased due to the limited information of seasonal catch. One way to overcome these obstacles is through culture activities. The provision of seeds is an important link in the culture system, therefore the study of the spawning process and larval development is an important requirement for the development of larval rearing techniques. This study aims to determine the development process of juvenil eggs and the survival rate of tiger snails reared in the laboratory.. The study was conducted at the Laboratory of Marine Farm Subdivision in Kudus, Pt Pura Bahari, Jepara Regency. This sudy used experimental method with descriptive data analysis. Adult tiger snails were caught from Bunga waters, Demak. The snails were reared in a rectangular tube filled with 15 cm filtered sea water and 5 cm of sand. Egg capsules were reared in a 4 liters circular tube with continuous aeration. The hatched larvae were reared in a 300 liters circular tube filled with filtered seawater, continuously aerated and fed with Chlorella plankton . Our result showed that tiger snails spawn naturally and produce egg capsules. The incubation period for the capsule is 6 days, then develop into veliger larva for 12 days. The veliger larvae metamorphosed,and become juvenil. The lowest survival rate observed in the veliger stage. The survival rate of the egg and the intracapsular trochopore stages were quite high (tube I = 98.413%; tube II = 98.238%; tube III = 90.476%), then the lowest was in the veliger stage (tube I = 3,468%; tube II = 2.603%; tube III = 2,598%) and the juvenil stage is quite high compared to the previous phase (tube I = 3,413%; tube II = 2,479%; tube III = 2,351%).